Teaching in disruptive bodies: finding joy, resistance and embodied knowing through collaborative critical praxis. Issue 2 (7th February 2020) - Case, Alissa; Joubert, Ezekiel
Abstract: In the current political moment, a collision of a post-racial/diversity politics and the era of Trump, highlights the multiple risks of engaging in social justice pedagogies within teacher preparation. The era of Trump is defined by the dismantling of civil rights accompanied by unapologetic and overt displays of violence. In teacher education classrooms, these contradictory realities underscore the tenor of conversations on justice and education. Thus, for teachers in non-normative bodies this very moment exacerbates the risks of unveiling systems of oppression. This essay juxtaposes how two teacher educators imagine their bodies as tools for resistance while simultaneously having their bodies resisted. They propose a collaborative critical praxis as an intervention, a way to embody an alternative way of knowing and being that engages and disrupts contradictions in and violences upon non-normative bodies in teacher education. Using this method, the authors discuss both implications and possibilities of resistance for teacher preparation classrooms and pedagogy.